Profile of thyroid hormones in breast cancer patients - Saraiva,P.P. (2005)
Estrogen involvement in breast cancer has been established; however, the association between breast cancer and thyroid diseases is controversial. Estrogen-like effects of thyroid hormone on breast cancer cell growth in culture have been reported. The objective of the present study was to determine the profile of thyroid hormones in breast cancer patients. Serum aliquots from 26 patients with breast cancer ranging in age from 30 to 85 years and age-matched normal controls (N = 22) were analyzed for free triiodothyronine (T3F), free thyroxine (T4F), thyroid-stimulating hormone (TSH), antiperoxidase antibody (TPO), and estradiol (E2). Estrogen receptor ß (ERß) was determined in tumor tissues by immunohistochemistry. Thyroid disease incidence was higher in patients than in controls (58 vs 18%, P < 0.05). Subclinical hyperthyroidism was the most frequent disorder in patients (31%); hypothyroidism (8%) and positive anti-TPO antibodies (19%) were also found. Subclinical hypothyroidism was the only dysfunction (18%) found in controls. Hyperthyroidism was associated with postmenopausal patients, as shown by significantly higher mean T3 and T4 values and lower TSH levels in this group of breast cancer patients than in controls. The majority of positive ERß tumors were clustered in the postmenopausal patients and all cases presenting subclinical hyperthyroidism in this subgroup concomitantly exhibited Erß-positive tumors. Subclinical hyperthyroidism was present in only one of 6 premenopausal patients. We show here that postmenopausal breast cancer patients have a significantly increased thyroid hormone/E2 ratio (P < 0.05), suggesting a possible tumor growth-promoting effect caused by this misbalance.